Fostering as an Alternative Sanction for Juveniles in the Perspective of Child Protection in Indonesia - Erdianti, Ratri Novita; Al-Fatih, Sholahuddin (Universitas Negeri Semarang, 2019)
Crimes committed by juveniles today continue to grow, as well as various law enforcement approaches. Juveniles as legal subjects have special attention not only in matters of children’s rights but also in the punishment of children. Various crimes committed by juveniles occur a lot and lead to no longer what is called juvenile delinquency, but a serious crime. The Child Protection Act and the Child Criminal Justice System Law explicitly regulate the protection of children’s rights in the context of human rights. Fostering sanctions for juveniles are one of the ways that are encouraged compared to providing severe criminal sanctions, while here another criminal law is a double-edged sword and ultimum remedium. This paper examines efforts to guide children as an alternative sanction in juvenile criminal law. Studies in this paper include studies of Child Criminal Law, Criminal Law, Human Rights, and the Law on Child Protection.